Between Chaos and Liberty: Chinese Uses of the French Revolution of 1789 - Bender De Moniz Bandeira, Egas Bernard (Alternative Representations of the Past: The Politics of History in Modern China, 2020)
This chapter traces the trajectory of one of the most emblematic events of modern history, the French Revolution of 1789, in Chinese political debates from late Qing to contemporary times. It shows that the French Revolution has been appropriated and used by Chinese actors—intellectuals, politicians, students, and others—in the light of their own historical experiences and for widely varying discursive objectives. It has been referenced in China both for the ideals it espoused and for the bloodshed and instability that it brought about in late 18th century France. Thus, it has not only served as an inspiration and a point of comparison for China’s own revolutions, chiefly the republican revolution of 1911, or as a democratic inspiration for Chinese intellectuals. Representations of the French revolution as an event of chaos and brutality have just as often been used by revolutionists to search for more suitable revolutionary models, as well as by conservative intellectuals and governments to debate reforms designed to prevent instability and political strife. Ultimately, the chapter shows that landmark events such as the French Revolution are far from being exclusive memories of the West. Rather, their diverse Chinese uses have become local refractions of global elements of collective memory.